A Study on Invitro to Measure the Shear Bond Strength of Glass Ionomer Cement Bound to Mineral Trioxide Aggregate - Roseka, Dr; Mittal, L; Gupta, YK; Anamika, Dr (Bangladesh Journal of Dental Research & Education, 2014)
DOI: http://dx.doi.org/10.3329/bjdre.v4i1.18007 Bangladesh Journal of Dental Research & Education Vol.4(1) 2014; 1-3